Effect of Heat Treatments on Microbial Load and Associated Changes to β‐Glucan Physicochemical Properties in Whole Grain Barley. Issue 2 (9th September 2016) - Boyd, Lindsey; Holley, Rick; Storsley, Joanne; Ames, Nancy
Abstract : Health claims for barley β‐glucan (BG) have prompted the development of food products containing barley; however, some new products (such as milled grain used without a cook step, as in a smoothie) do not use any form of heat treatment during processing or prior to consumption, which could affect microbial safety and potential health benefits. The aims of this research were to evaluate current commercial barley products for microbial counts and BG characteristics and to determine the effects of different heat treatments on these attributes in whole grain barley samples. Three heat treatments (micronization, roasting, and conditioning) were performed on three cultivars of barley (CDC Rattan, CDC McGwire, and CDC Fibar). The microbial quality was measured with standard plate count (SPC), mold and yeast count (MYC), and coliforms or Escherichia coli . Only four of the 17 commercial barley products tested met acceptable microbial limits used in this study. All three heat treatments applied to the barley samples in this study reduced SPC, MYC, and coliforms to an acceptable level. BG was extracted with an in vitro digestion method to determine its viscosity, molecular weight (MW), and solubility. All three heat treatments produced BG extracts with high viscosity and MW compared with untreated barley. Overall, heat treatments improved both the safety and the potential health benefits from soluble BG in whole grain barley.